2021
DOI: 10.3390/electronics10020180
|View full text |Cite
|
Sign up to set email alerts
|

Device and Circuit Exploration of Multi-Nanosheet Transistor for Sub-3 nm Technology Node

Abstract: A multi-nanosheet field-effect transistor (mNS-FET) device was developed to maximize gate controllability while making the channel in the form of a sheet. The mNS-FET has superior gate controllability for the stacked channels; consequently, it can significantly reduce the short-channel effect (SCE); however, punch-through inevitably occurs in the bottom channel portion that is not surrounded by gates, resulting in a large leakage current. Moreover, as the size of the semiconductor device decreases to several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In our previous study on BO thickness based on the presence or absence of BO application and substrate [8], we confirmed that BO successfully reduced the leakage current. As an extension of that previous study, the current study tried to optimize PTS doping and BO at the same time; since PTS doping and BO application include capacitancevoltage (C-V) characteristics in addition to current-voltage (I-V) characteristics, the effect of reducing leakage current on various logic/memory circuits was investigated.…”
Section: Introductionsupporting
confidence: 76%
“…In our previous study on BO thickness based on the presence or absence of BO application and substrate [8], we confirmed that BO successfully reduced the leakage current. As an extension of that previous study, the current study tried to optimize PTS doping and BO at the same time; since PTS doping and BO application include capacitancevoltage (C-V) characteristics in addition to current-voltage (I-V) characteristics, the effect of reducing leakage current on various logic/memory circuits was investigated.…”
Section: Introductionsupporting
confidence: 76%
“…In addition, with respect to source/drain (S/D) modules, the contact depth as well as inner spacer thickness needs to be optimized [ 8 , 9 ]. It should be noted in particular that, unlike bulk FinFETs, which have already been mass produced, NS FETs have a parasitic channel underneath the first floor nanosheet [ 10 , 11 , 12 , 13 ]. Hence, even though NS FETs have multiple channels that are completely surrounded by metal gates (i.e., GAA), increased I OFF stemming from the parasitic channel is inevitable.…”
Section: Introductionmentioning
confidence: 99%
“…Extension work to establish the precise device models for 3D devices such as Fin-FETs [30][31][32] or gate-all-around FETs [33,34] is still outstanding. Even though the device format is multi-nano-sheet (mNS) or multi-bridge-channel [16,[35][36][37], this concept of providing a great set of device models considering the contribution of the gate field is rather feasible. Of course, entering the 10-nm process or beyond, the current performance can be disturbed by quantum confinement effects [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to give this deeper consideration, modulating all the parameters (V DS , V GS , and L mask ) at once to fully satisfy the µ eq correlated to the V DS , V GS , and channel length on drawn mask L mask . Moreover, by consolidating the adjustment of V DS and L mask correlated to the horizontal electric field and V GS influencing the vertical electric field, the drive current of MOSFETs can be more meaningful and beneficial in providing a set of accurate nano-node device models, especially beyond 28-nm node fabrication or entering 3-nm node processes [13][14][15][16]. The gate bias, which conducts the moving carriers in the channel, induces more carrier scattering, especially in surface roughness.…”
Section: Introductionmentioning
confidence: 99%